Fracture Toughness and Oxidation Resistance of Ti-Al-N Coatings on Stainless Steel Substrates; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Akulinkin A.; Shugurov A.; Panin A. V. Alexey Viktorovich; Sergeev V.; Cheng C. -H. (2016, 2016)
Title screen